Circulating miR-375 as a novel prognostic marker for metastatic medullary thyroid cancer patients. Issue 3 (March 2018) - Romeo, Paola; Colombo, Carla; Granata, Roberta; Calareso, Giuseppina; Gualeni, Ambra Vittoria; Dugo, Matteo; De Cecco, Loris; Rizzetti, Maria Grazia; Zanframundo, Angela; Aiello, Antonella; Carcangiu, Maria Luisa; Gloghini, Annunziata; et al.
Abstract : This study aimed to identify circulating miRNAs as novel non-invasive biomarkers for prognosis and vandetanib response in advanced medullary thyroid cancer (MTC) patients. We prospectively recruited two independent cohorts of locally advanced/metastatic MTC patients including a subgroup of vandetanib-treated subjects: a discovery cohort ( n = 20), including matched plasma/tissue samples ( n = 17/20), and a validation cohort, yielding only plasma samples ( n = 17). Plasma samples from healthy subjects ( n = 36) and MTC patients in remission ( n = 9) were used as controls. MTC ( n = 17 from 8 patients included in discovery cohort) and non-neoplastic thyroid specimens ( n = 3) were assessed by microarray profiling to identify candidate circulating miRNAs. qRT-PCR and in situ hybridization were carried out to validate the expression and localization of a selected miRNA within tissues, and qRT-PCR was also performed to measure miRNA levels in plasma samples. By microarray analysis, we identified 51 miRNAs differentially expressed in MTC. The most overexpressed miR, miR-375, was highly expressed by C cells compared to other thyroid cells, and more expressed in MTC than in reactive C-cell hyperplasia. MTC patients had significantly higher miR-375 plasma levels than healthy controls ( P < 0.0001) and subjects in remission ( P = 0.0004) as demonstrated by qRT-PCR analysis. miR-375 plasma levels were not predictive of vandetanib response, but, notably, high levels were associated with significantly reduced overall survival (HR 10.61, P < 0.0001) and were a strong prognostic factor of poor prognosis (HR 6.24, P = 0.00025) in MTC patients. Overall, our results unveil plasma miR-375 as a promising prognostic marker for advanced MTC patients, to be validated in larger cohorts.